Aqueous dispersions of lipid nanoparticles wet hydrophobic and superhydrophobic surfaces - Kumar, Manoj; Kulkarni, Mayuresh A.; Chembu, Narendiran G.; Banpurkar, Arun; Kumaraswamy, Guruswamy (Soft Matter, 2018)
Efficient delivery of aqueous sprays to hydrophobic surfaces is the key technological challenge in a wide variety of applications, including pesticide delivery to plants. To account for losses due to bouncing of pesticide sprays off hydrophobic leaf surfaces, a large excess of pesticide is typically employed, resulting in environmentally hazardous run-offs that contaminate soil and ground water. We demonstrate that aqueous dispersions of glycerol monooleate nanoparticles, called cubosomes, wet hydrophobic and superhydrophobic surfaces and adhere to them. Cubosomes comprise glycerol monooleate lipid molecules self-assembled into a double diamond cubic phase, that form stable aqueous dispersions that are sterically stabilized using amphiphilic block copolymers. We use high speed imaging to monitor the spreading and retraction of aqueous drops impinged on model hydrophobic substrates and on superhydrophobic lotus leaves. We show that cubosomes diffuse to hydrophobic substrates and reorganize to form a thin, approximate to 2 nm adsorbed lipid layer during the millisecond time scales that characterize drop impact. This adsorbed film drastically reduces the water contact angle, transforming the hydrophobic surface to hydrophilic, thus facilitating retention of the aqueous drop on the surface. Aqueous drops of cubosomes impinged at low velocities on inclined natural superhydrophobic lotus leaf surfaces do not roll off, unlike drops of water or surfactant solutions. When sprayed on inclined lotus leaves, corresponding to the case of high velocity drop impingement, cubosome dispersions form a continuous wetting film. Our results have important implications for efficient, environment-friendly delivery of pesticide sprays.